2017
DOI: 10.1002/anie.201706769
|View full text |Cite
|
Sign up to set email alerts
|

The N‐Terminal Domain of ALS‐Linked TDP‐43 Assembles without Misfolding

Abstract: Transactivation response element (TAR) DNA-binding protein 43 (TDP-43) misfolding is implicated in several neurodegenerative diseases characterized by aggregated protein inclusions. Misfolding is believed to be mediated by both the N- and C-terminus of TDP-43; however, the mechanistic basis of the contribution of individual domains in the process remained elusive. Here, using single-molecule fluorescence and ensemble biophysical techniques, and a wide range of pH and temperature conditions, we show that TDP-43… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 27 publications
3
45
0
Order By: Relevance
“…Several groups have reported that TDP‐43 NTD mediates assembly into dimers or other higher‐order structures (Shiina et al , ; Chang et al , ; Wang et al , ), though the details of the assembly have only recently begun to be visualized with atomistic resolution (Afroz et al , ; Jiang et al , ; Mompean et al , ; Tsoi et al , ). Recombinant TDP‐43 NTD (in our case: residues 1–80, with only three additional N‐terminal residues, GHM, resulting from the cloning strategy and cleavage with TEV protease) is highly soluble when expressed and purified from bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Several groups have reported that TDP‐43 NTD mediates assembly into dimers or other higher‐order structures (Shiina et al , ; Chang et al , ; Wang et al , ), though the details of the assembly have only recently begun to be visualized with atomistic resolution (Afroz et al , ; Jiang et al , ; Mompean et al , ; Tsoi et al , ). Recombinant TDP‐43 NTD (in our case: residues 1–80, with only three additional N‐terminal residues, GHM, resulting from the cloning strategy and cleavage with TEV protease) is highly soluble when expressed and purified from bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Single-molecule measurements coupled to bulk biophysical techniques indicated that TDP-43 converts into amyloid-like fibrils following two distinct pathways. In one pathway, the CTDs of different molecules assemble directly [ 34 ]. In a second, parallel, pathway, fibrillation is induced by the NTD following a two-step process in which first the NTD domains dock, then the CTDs lock the molecules into an amyloid-like aggregate [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In one pathway, the CTDs of different molecules assemble directly [ 34 ]. In a second, parallel, pathway, fibrillation is induced by the NTD following a two-step process in which first the NTD domains dock, then the CTDs lock the molecules into an amyloid-like aggregate [ 34 ]. This is consistent with a previous finding that the first 10 residues of the TDP-43 sequence are crucial for both the folding and misfolding of the protein [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein valency increases with the presence of oligomerization domains. For example, TDP-43, a highly expressed nuclear RBP, contains an N-terminal domain that forms oligomers (117,(121)(122)(123)(124). Recently, Wang et al (117) established that polymerization of the N-terminal domain promotes LLPS of TDP-43 in vitro and that a single phosphomimetic mutant in the N-terminal domain can reduce the propensity of TDP-43 to phase separate.…”
Section: Oligomerization Domainsmentioning
confidence: 99%